2003
DOI: 10.1007/s00024-003-2407-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Earthquake Strong Ground Motion

Abstract: -Some underwater landslides are triggered by strong ground motions caused by earthquakes. This paper reviews current concepts and trends in the characterization of strong ground motion. Improved empirical ground motion models have been derived from a strong motion data set that has grown markedly over the past decade. However, these empirical models have a large degree of uncertainty because the magnitude-distance-soil category parameterization of these models often oversimplifies reality. This reflects the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…The influence of the near fault rupture directivity for the strong ground motion pattern has been discussed both from the observation and numerical simulation (Somerville and Graves, 2003). For example, Somerville and Grave (2003) found that, at the rupture propagation direction (forward direction), the near fault particle motion in the normal direction to the fault behaviors as a pulse function with a very short time duration.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…The influence of the near fault rupture directivity for the strong ground motion pattern has been discussed both from the observation and numerical simulation (Somerville and Graves, 2003). For example, Somerville and Grave (2003) found that, at the rupture propagation direction (forward direction), the near fault particle motion in the normal direction to the fault behaviors as a pulse function with a very short time duration.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…In terms of real observations and numerical simulation of earthquake faulting, Somerville and Graves (2003) has investigated the characteristics of near fault ground motion related to the rupture directivity. For example, in the analyzing of the 1992, M S 7.5, Landers earthquake in California, they had found that in the forward direction of rupture, the particle displacement in fault normal direction appears a pulse shaped motion near the fault.…”
Section: Simulation Of Sanhe-pinggu Earthquakementioning
confidence: 99%
“…In Mentougou and Fangshan areas, the ground motions have shown the unusual high peak values of accelerations compared with the results in Figure 8 which was derived from the traditional attenuation relations. Figure 8 gives the mean values of peak ground acceleration derived from five attenuation relations used in the Central and East United States, which were developed by Atkinson and Boore (1995), Campbell (2003), Frankel et al (1996, Somerville and Graves (2003), and Toro et al (1997). Although it is not completely suitable to use these attenuation relations in the description of ground motion characteristics in China, because of lacking sophisticated attenuation relation models, we use these attenuation model here only for the comparison purpose.…”
Section: Simulation Of Sanhe-pinggu Earthquakementioning
confidence: 99%
“…Strong ground motions may destabilize slopes by overtopping static gravity forces with transient inertial forces, building up pore water pressure within slope materials, and therefore weakening their shear resistance. SOMERVILLE and GRAVES (2003) review the current concepts in engineering seismology and the recent advances in modeling earthquake strong ground motions. They provide a useful list of state-of-the-art references on the modeling of strong ground motion.…”
Section: Modeling Earthquake Ground Motions and Source Characteristicsmentioning
confidence: 99%